The art of electronics - Horowitz, Paul 1942-; Hill, Winfield (New York, NY Cambridge University Press, 2015)
At long last, here is the thoroughly revised and updated third edition of the hugely successful The Art of Electronics. It is widely accepted as the best single authoritative book on electronic circuit design, both analog and digital. The art of electronics is explained by stressing the methods actually used by circuit designers--a combination of some basic laws, rules of thumb, and nonmathematical treatment that encourages understanding why and how a circuit works.
Foundations -- Bipolar transistors -- Field-effect transistors -- Operational amplifiers -- Precision circuits -- Filters -- Oscillators and timers -- Low-noise techniques -- Voltage regulation and power conversion -- Digital logic -- Programmable logic devices -- Logic interfacing -- Digital meets analog -- Computers, controllers, and data lLinks -- Microcontrollers -- Appendix A. Math review -- Appendix B. How to draw schematic diagrams -- Appendix C. Resistor types -- Appendix D. Thévenin's Theorem -- Appendix E. LC Butterworth Filters -- Appendix F. Load Lines -- Appendix G. The Curve Tracer -- Appendix H. Transmission Lines and Impedance Matching -- Appendix I. Television : a compact tutorial -- Appendix J. SPICE primer -- Appendix K. "Where do I go to buy electronic goodies?" -- Appendix L. Workbench instruments and tools -- Appendix M. catalogs, magazines, databooks -- Appendix N. Further reading and references -- Appendix O. The oscilloscope -- Appendix P. acronyms and abbreviation.
Includes bibliographical references and index.
Keywords: Electronics; Electronic circuit design